2022
DOI: 10.1099/mgen.0.000828
|View full text |Cite
|
Sign up to set email alerts
|

Novel internalin P homologs in Listeria

Abstract: Listeria monocytogenes (Lm) is a bacterial pathogen that causes listeriosis in immunocompromised individuals, particularly pregnant women. Several virulence factors support the intracellular lifecycle of Lm and facilitate cell-to-cell spread, allowing it to occupy multiple niches within the host and cross-protective barriers, including the placenta. One family of virulence factors, internalins, contributes to Lm pathogenicity by inducing specific uptake and conferring t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Identifying and characterizing the complete molecular systems involved in such processes requires functional knowledge of the proteins involved. Many studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] have demonstrated the power of phylogenetic and molecular evolutionary analysis in determining the molecular functions of such proteins. A variety of individual tools exist for protein sequence similarity searches or ortholog detection, delineating co-occurring domains (domain architectures), and building multiple sequence alignments and phylogenetic trees.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying and characterizing the complete molecular systems involved in such processes requires functional knowledge of the proteins involved. Many studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] have demonstrated the power of phylogenetic and molecular evolutionary analysis in determining the molecular functions of such proteins. A variety of individual tools exist for protein sequence similarity searches or ortholog detection, delineating co-occurring domains (domain architectures), and building multiple sequence alignments and phylogenetic trees.…”
mentioning
confidence: 99%
“…MolEvolvR is a generalized web server of this web-app. To demonstrate its broad applicability, we have applied the approach underlying MolEvolvR to study several systems, including proteins/operons in zoonotic pathogens, e.g., nutrient acquisition systems in Staphylococcus aureus 4,5 , novel phage defense system in Vibrio cholerae 6 , surface layer proteins in Bacillus anthracis 7 , helicase operators in bacteria 8 , and internalins in Listeria spp 9 . We have included a few pre-loaded examples in MolEvolvR for users to explore in addition to help pages and FAQ.…”
mentioning
confidence: 99%